Republic of Moldova : 2021 Article IV Consultation and Requests for an Arrangement under the Extended Fund Facility and an Arrangement under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Moldova. (IMF Staff Country Reports; Country Report, 2022)
The 2016-20 ECF/EFF helped rehabilitate Moldova's banking sector, bolstering macro-financial stability. However, the COVID-19 pandemic, drought in 2020, and the ongoing surge in global energy prices, have slowed economic activity, intensified downside risks, and complicated policy making. While emergency financial assistance under a blended RCF/RFI (100 percent of quota) and SDR allocation (USD 236 million) helped cushion the pandemic's impact, Moldova remains among the poorest countries in Europe with long-standing governance and structural weaknesses inhibiting income convergence.